2019
DOI: 10.1093/cid/ciz948
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus RNA Is Commonly Detectable in Rectal and Nasal Fluids of Patients With High Viremia

Abstract: Background Increasing numbers of hepatitis C virus (HCV) infections among men who have sex with men (MSM) are being observed in the Western world. The actual routes of HCV transmission during high-risk sex practices and associated drug use remain poorly understood. Methods Forty-seven patients with HCV were prospectively enrolled. Rectal and nasal swabs were collected to quantify HCV-RNA levels within rectal and nasal fluids.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 40 publications
1
14
0
3
Order By: Relevance
“…A unique aspect of our study was the inclusion of persons actively using drugs by injection and noninjection routes. Although IDU is a known risk factor for HCV transmission, noninjection drug and alcohol use are also very common, and these may present challenges to ensuring medication adherence, treatment completion [ 21 , 22 ], and potentially contribute to reinfection depending on drug administration route and other behaviors [ 35 ]. Stimulant injection has been identified as a risk factor for poor DAA adherence [ 7 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…A unique aspect of our study was the inclusion of persons actively using drugs by injection and noninjection routes. Although IDU is a known risk factor for HCV transmission, noninjection drug and alcohol use are also very common, and these may present challenges to ensuring medication adherence, treatment completion [ 21 , 22 ], and potentially contribute to reinfection depending on drug administration route and other behaviors [ 35 ]. Stimulant injection has been identified as a risk factor for poor DAA adherence [ 7 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we had very limited information on specific risk, since only information on the suspected route of HCV transmission was available. Nevertheless, previous studies have demonstrated that the vast majority of Austrian HCV-infected MSM engaged in sexualized drug use and condomless anal intercourse 9 -two well-established high-risk practices for HCV acquisition. Another typical marker for increased risk for HCV transmission is positive HIV status.…”
Section: F I G U R E 2 Overall Incident Acute Hcv Infections During T...mentioning
confidence: 99%
“…This is in line with reports from other European centers describing a high incidence/prevalence of HCV infection [ 3 ], even in times of unrestricted access to direct-acting antiviral (DAA) treatment [ 4 ], not only in HIV-positive MSM but also in HIV-negative MSM, especially if they take pre-exposure prophylaxis (PrEP) [ 5 , 6 ]. Unprotected anal intercourse and nasal and/or intravenous drug use are considered major modes of transmission for HCV in MSM, and respective risk behavior is commonly observed in the Viennese MSM population [ 7 ]. Early treatment of HCV-infected MSM has been shown to be highly effective [ 1 ], even among patients with ongoing drug use [ 8 ].…”
Section: Introductionmentioning
confidence: 99%